Perspectives and provocations in early childhood education. Volume 3 - Felderman, Carol Branigan; Kissel, Brian T.; Nash, Kindel Turner (Early childhood education assembly., 2014)
In classrooms where children's voices are valued, young readers and writers possess power. Their ability to exert this power through literacy is especially evident in classrooms where children, who are traditionally marginalized, can use their voices to be change agents. In this third volume of Perspectives and Provocations in Early Childhood Education, the authors' stories explore students' agentive power to change themselves, their teachers, school administrators, and the world.